PENGARUH LABELISASI HALAL DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN PRODUK UMKM PONDOK JAMUR TIRAM ENDANG MUARA BULIAN KABUPATEN BATANGHARI - Alfazri Rahmadani; M. Andriansyah (Jurnal Cakrawala Ilmiah, 2025)
Many business actors do not yet have business permits, which has a big influence on the development of a business. and halal labeling can also greatly influence consumer buying interest, where the majority of consumers are Muslims who pay attention to the halalness of a product when they want to buy it. and nowadays it is very important to build a brand image well to get attention and validation from consumers.This research approach is descriptive quantitative, because this research is presented with numbers. In this descriptive quantitative research, intervention or treatment is carried out in research. Quantitative research includes descriptive research, which describes something with statistics or numbers and is analyzed to find answers to the formulation of a problem in research. This research is descriptive quantitative research with a survey approach. The sample used for the research sample was 80 people.Conclusion: Halal Labeling, and Brand Image together influence Consumer Purchase Intentions. To answer the fourth hypothesis, a simultaneous test was carried out (f test). Based on the test results, it shows that partially the halal labeling variables (X1), brand image (X2) have a significant effect on consumer buying interest, which means that if a shop's brand image is better, it will have a positive effect on consumer buying interest. This is supported by the results of the t test and f test. So it can be seen that the brand image and halal labeling variables have a positive effect on the dependent variable consumer buying interest (Y).